‘CINEMA’ IN FORMATION OF CULTURAL IDENTITIES: A STUDY ON THE ETHNOGRAPHIC FILMS AND PEOPLE’S PERCEPTION ON TULU FILMS - M, Darshan B.; Prasad, Ramya K (International Journal of Psychosocial Rehabilitation, 2020)
Indian cinema enjoys a magnificent status in world cinema, as it produces the highest number of cinemas in different languages every year, portraying the various elements of culture even in minority speaking languages. The objective of the paper is to analyze the perception of ethnographic films with specific reference to Tulu cinema. The researcher has made an attempt to critically analyze how the culture of Tulu Nadu is portrayed in Tulu films and how the wider public responds to it, as a reflection on the essence of their life.To analyze the perception of ethnographic films with specific reference to Tulu cinema, the researcher has undertaken an audience analysis among 400 respondents using purposive sampling survey method, a focus group discussion among the respondents of Tulu Nadu and a qualitative content analysis on two Tulu movies which fall into the category of ethnographic films. The results indicate that there is an instant acceptance and relativity towards the movies and portrayal of the culture. The implications of the present study indicate the need to understand the taste of Tuluvas in the depiction of their own culture by the filmmakers.In the overflew of varied genres, modernity and the tendency to imitate developed mainstream language movies, Tulu films in the modern times are losing its identity and being away from the depiction of real-life of Tulu Nadu. This has to be addressed pragmatically for the sustenance of Tulu films as well as creating more unique pieces of films which portrays the real essence of Tuluva culture. Ethnographic Cinema act like the visual manifestation of anthropological practice organized into a linear and moving media for portraying the cultural dimensions and diversity of people, communities and regions. Tulu is an ancient language spoken in coastal Karnataka. Tulu cinema is one of the typical examples for a regional film industry with a short history and minimal resources. And hence the need for studying the perceptions of such ethnographic films in Tulu Cinema.